THE EFFECTIVENESS OF DEVELOPING METACOGNITIVE SKILLS IN PRESCHOOL CHILDREN THROUGH FAIRY TALE THERAPY - Mukhiddinova Dilfuza Sherdor qizi (Bright Mind Publishing, 2026)
This study examines an experimental program aimed at developing metacognitive skills in preschool children aged 5–7 through fairy tale therapy technologies. The purpose of the experimental research was to design and validate methodological recommendations that address identified gaps in preschool instructional practice and improve the effectiveness of the didactic process. The experiment was conducted from 2023 to 2026 and implemented in three stages: diagnostic (ascertaining), formative, and final statistical. Following baseline diagnostics, children were divided into experimental and control groups: the control group continued with traditional instructional approaches, while the experimental group participated in a structured set of fairy tale therapy–based activities supported by author-developed plans and technological guidelines for educators.
Keywords: Fairy tale therapy; metacognitive skills; preschool education; reflection; experimental research; play-based learning; formative intervention; pedagogical technology; assessment criteria; educational effectiveness.